Het Experiment in de Nederlandse film. - ten Zijthoff, Reg; de Mol, Paul; Rubin, Peter (Amsterdam : Stedelijk Museum, 1985)
Blank, Matthijs ; Boezem, Marinus ; Dibbets, Jan ; van Elk, Ger ; Hoover, Nan ; van der Keuken, Johan ; Luyken, Edward ; van Munster, Jan ; de Nooijer, Paul ; etc.
Nederlands
boek
Keywords: Nederland